(untitled) (Texas Journal of Engineering and Technology, 2025)
This article extensively covers the issues of stable and reliable voltage and frequency parameter control in modern power systems. With the widespread use of renewable energy sources in the power sector, such as solar and wind power plants, hybrid systems integrated with traditional centralized power grids are emerging. One of the main problems in such systems is the effective elimination of voltage and frequency disturbances caused by variability in production due to natural factors. The article notes that photovoltaic panels can cause short-term but significant voltage fluctuations due to rapid changes in light flux. This can reduce the reliability of equipment in the grid and the quality of supply for users. Therefore, it is necessary to implement highly accurate automated control systems in power grids